The Effect of Price, Product Quality and Promotion on Purchasing Decisions at UMKM Baso Aci Mba Pit in Jonggol - R.R Wening Ken Widodasih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Unique promotion can use creative media so that it becomes a factor to influence consumers in making purchases of the product being promoted. This study aims to determine the effect of price, product quality and promotion on purchasing decisions at UMKM Baso Aci Mba Pit. Sampling of this study by nonprobability sampling method. Data analysis in this study used computer software SPSS version 23. The results of this study were that price had a significant effect on purchasing decisions with a sig analysis value of 0.022<0.05, product quality had a significant effect on purchasing decisions with a sig analysis value of 0.017<0.05, promotion has a significant effect on purchasing decisions with a sig analysis value of 0.000 <0.05, price, product quality and promotions simultaneously have a significant effect on purchasing decisions with an F sig analysis value of 0.000 <0.05.